Arsenic (III) removal from drinking water using rust waste sand filter - Uddin, Shahab; Alam, Md. Akramul (Italian journal of engineering geology and environment, 2019)
<span data-sheets-value="{"1":2,"2":"The present study has contributed to the present state of knowledge on the effects of Rust Waste Sand (RWS) on removing arsenic from water. The main contributions of the research are evaluation and investigation the performance of Rust Waste Sand (RWS) on removing arsenic (III) from water, and enhancement of new research area and idea on removing arsenic from water using Rust waste. This paper describes experiments in which Rust Waste Sand (RWS) filter was used to study the removal of arsenic. This filter media was prepared with rust passing through #30 no ASTM sieve and local sand of FM 2.605 with the ratio of 2:1 by weight, and column test was performed to assess the effectiveness and suitability. Ten cycles of column tests were conducted to evaluate the performance of RWS filter media. The arsenic removal by RWS filter media with was significant. Performance of RWS filter in removing As (III) for pH of 6.5, 7.0 and 7.5 water with respect to contract time showed a better result for pH 6.5 and followed by pH 7.0 and pH 7.5. In removing 50% As (III) from water of pH 6.5, 7.0 and 7.5 the contact time were 225, 290 and 350 s respectively whereas iron-oxide coated sand (IOCS) required 1,380 s for the water of pH 7.5-7.8. RWS filter is more effective in removing As (III) from water abruptly than iron-oxide coated sand and others iron based adsorptions materials. Also, it had been investigated that at certain cycle of filtration total iron leaching from the filter in the water were noticed and this concentration was very many low than standard guidelines. The results of column studies showed that RWS filter media could be effectively used as both very low cost and user friendly technology to achieve less than drinking water standard level of As concentration."}" data-sheets-userformat="{"2":15233,"3":{"1":0},"10":1,"11":3,"12":0,"14":{"1":2,"2":0},"15":"Arial","16":8}">The present study has contributed to the present state of knowledge on the effects of Rust Waste Sand (RWS) on removing arsenic from water. The main contributions of the research are evaluation and investigation the performance of Rust Waste Sand (RWS) on removing arsenic (III) from water, and enhancement of new research area and idea on removing arsenic from water using Rust waste. This paper describes experiments in which Rust Waste Sand (RWS) filter was used to study the removal of arsenic. This filter media was prepared with rust passing through #30 no ASTM sieve and local sand of FM 2.605 with the ratio of 2:1 by weight, and column test was performed to assess the effectiveness and suitability. Ten cycles of column tests were conducted to evaluate the performance of RWS filter media. The arsenic removal by RWS filter media with was significant. Performance of RWS filter in removing As (III) for pH of 6.5, 7.0 and 7.5 water with respect to contract time showed a better result for pH 6.5 and followed by pH 7.0 and pH 7.5. In removing 50% As (III) from water of pH 6.5, 7.0 and 7.5 the contact time were 225, 290 and 350 s respectively whereas iron-oxide coated sand (IOCS) required 1,380 s for the water of pH 7.5-7.8. RWS filter is more effective in removing As (III) from water abruptly than iron-oxide coated sand and others iron based adsorptions materials. Also, it had been investigated that at certain cycle of filtration total iron leaching from the filter in the water were noticed and this concentration was very many low than standard guidelines. The results of column studies showed that RWS filter media could be effectively used as both very low cost and user friendly technology to achieve less than drinking water standard level of As concentration.